2023
DOI: 10.3390/separations10090513
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Removal of Crystal Violet Dye Utilizing Greenly Synthesized Iron Oxide Nanoparticles

Mohamed Taha Yassin,
Fatimah O. Al-Otibi,
Abdulaziz A. Al-Askar

Abstract: The presence of synthetic industrial dyes in the environment poses significant risks to aquatic ecosystems, human health, and economies. This study aims to synthesize iron oxide nanoparticles (IONPs) using a green method, analyze them using physicochemical techniques, and examine the effectiveness with which they photocatalytically degrade crystal violet dye in sunlight. Fourier transform infrared spectroscopy (FTIR) analysis revealed that the biogenic IONPs showed a UV peak at a wavelength of 241 nm, with fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 70 publications
(80 reference statements)
0
0
0
Order By: Relevance
“…Figure 8 shows a depiction of the chemical mechanism that produces these reactant species over two types of nanoparticles involved in different AOPs, resulting in the final degradation of pollutants into carbon dioxide and water. On the photocatalytic degradation of violet dye using iron oxide nanoparticles (IONPs), Yassin et al found that the removal efficiency of violet dye was concentration and time dependent, reaching a peak of 99.23% after 210 min of sunlight exposure [112]. Additionally, the green-based synthesis of IONPs in this study demonstrated relevant associated antioxidant activity, further emphasizing their potential in environmentally friendly approaches for eliminating industrial synthetic dyes and remediating contaminated environments and aquatic ecosystems.…”
Section: Environmental Remediationmentioning
confidence: 50%
“…Figure 8 shows a depiction of the chemical mechanism that produces these reactant species over two types of nanoparticles involved in different AOPs, resulting in the final degradation of pollutants into carbon dioxide and water. On the photocatalytic degradation of violet dye using iron oxide nanoparticles (IONPs), Yassin et al found that the removal efficiency of violet dye was concentration and time dependent, reaching a peak of 99.23% after 210 min of sunlight exposure [112]. Additionally, the green-based synthesis of IONPs in this study demonstrated relevant associated antioxidant activity, further emphasizing their potential in environmentally friendly approaches for eliminating industrial synthetic dyes and remediating contaminated environments and aquatic ecosystems.…”
Section: Environmental Remediationmentioning
confidence: 50%